Highly Ordered Self‐Assembly of Native Proteins into 1D, 2D, and 3D Structures Modulated by the Tether Length of Assembly‐Inducing Ligands. Issue 36 (7th June 2017) - Yang, Guang; Ding, Hong‐ming; Kochovski, Zdravko; Hu, Rongting; Lu, Yan; Ma, Yu‐qiang; Chen, Guosong; Jiang, Ming
Abstract: In nature, proteins self‐assemble into various structures with different dimensions. To construct these nanostructures in laboratories, normally proteins with different symmetries are selected. However, most of these approaches are engineering‐intensive and highly dependent on the accuracy of the protein design. Herein, we report that a simple native protein LecA assembles into one‐dimensional nanoribbons and nanowires, two‐dimensional nanosheets, and three‐dimensional layered structures controlled mainly by small‐molecule assembly‐inducing ligandsRnG ( n =1, 2, 3, 4, 5) with varying numbers of ethylene oxide repeating units. To understand the formation mechanism of the different morphologies controlled by the small‐molecule structure, molecular simulations were performed from microscopic and mesoscopic view, which presented a clear relationship between the molecular structure of the ligands and the assembled patterns. These results introduce an easy strategy to control the assembly structure and dimension, which could shed light on controlled protein assembly. Abstract : Another dimension to protein assembly : Native protein LecA is shown to self‐assemble into one‐dimensional nanoribbons and nanowires, two‐dimensional nanosheets, and three‐dimensional layered structures controlled mainly by the length of a small‐molecule assembly‐inducing ligand. By changing the number of repeating units in the ligand (from one to five) the dimensionality of the assemblies can be controlled without the need for protein engineering.